Bunuh Diri dalam Perspektif Sosiologi Agama dan Teologi Katolik - Yanto Sandy Tjang; Herkulana Mekarryani Soeryamassoka; Mayong Andreas Acin; Vensius Rico Novi Andry; Victoria Julianti Siska Ubeq; Theresia Lina Iswaraningsih; Yosephin Metauli Situmorang (Media: Jurnal Filsafat dan Teologi, 2026)
This article examines suicide from the perspectives of the sociology of religion and Catholic theology in order to understand its social, moral, and pastoral dimensions. The study employs a qualitative approach through interdisciplinary library research, integrating sociological theories of religion with theological reflections within the Catholic tradition. The analysis shows that suicide cannot be understood solely as an individual act but is closely related to social integration, communal solidarity, and the protective role of religious communities. From a theological perspective, Bunuh Diri Dalam Perspektif Sosiologi Agama dan Teologi KatolikCatholic teaching emphasizes the inherent dignity of the human person, the complexity of moral responsibility in situations of psychological suffering, and the primacy of divine mercy. The study argues that an interdisciplinary approach provides a more comprehensive framework for interpreting suicide and responding pastorally to those affected by it. It proposes a contextual pastoral response that includes spiritual accompaniment, compassionate pastoral care, and the strengthening of community support systems. Such an approach enables the Church to address the issue of suicide in a more humane, reflective, and pastorally responsible manner.